Influence of ion induced local Coulomb field and polarity on charge generation and efficiency in poly(3-hexylthiophene)-based solid-state dye-sensitized solar cells - Abrusci, A; Santosh Kumar, R; Al-Hashimi, M; Heeney, M; Petrozza, A; Snaith, H (2011)
Dye-sensitized solar cells (DSSC) are a realistic option for converting light to electrical energy. Hybrid architectures offer a vast materials library for device optimization, including a variety of metal oxides, organic and inorganic sensitizers, molecular, polymeric and electrolytic hole-transporter materials. In order to further improve the efficiency of solid-state dye-sensitized solar cells, recent attention has focused on using light absorbing polymers such as poly(3-hexylthiophene) (P3HT), to replace the more commonly used "transparent" 2,2′,7,7′-tetrakis-(N,N-di-p- methoxyphenyl-amine)9,9′spiro-bifluorene (spiro-OMeTAD), in order to enhance the light absorption within thin films. As is the case with spiro-OMeTAD based solid-state DSSC, the P3HT-based devices improve significantly with the addition of lithium bis(trifluoromethylsulfonyl)imide salts (Li-TFSI), although the precise role of these additives has not yet been clarified in solid-state DSCs. Here, we present a thorough study on the effect of Li-TFSI in P3HT based solid-state DSSC incorporating an indolene-based organic sensitizer termed D102. Employing ultrafast transient absorption and cw-emission spectroscopy together with electronic measurements, we demonstrate a fine tuning of the energetic landscape of the active cell components by the local Coulomb field induced by the ions. This increases the charge transfer nature of the excited state on the dye, significantly accelerating electron injection into the TiO2. We demonstrate that this ionic influence on the excited state energy is the primary reason for enhanced charge generation with the addition of ionic additives. The deepening of the relative position of the TiO2 conduction band, which has previously been thought to be the cause for enhanced charge generation in dye sensitized solar cells with the addition of lithium salts, appears to be of minor importance in this system. The cascade of photophysical events that occurs within the operating device when ions are incorporated in the dye-sensitized solar cells is described. It is demonstrated that the ionic influence on the excited state energy is the primary reason for enhanced charge generation and devices performance. Copyright © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.